O SUBESQUEMA [ADV DE EXCLUSÃO + SE] NO PORTUGUÊS BRASILEIRO - DIOGO AYANO BRAGA DA SILVA (2022)
The main objective of this dissertation is to describe the subscheme [ADV de exclusão + se] based on the notion that it integrates the network of conditional connectors and that the connectors instantiated by the subschema, somente se, só se and exceto se are restrictive connectors, differing them based on the meaning manifested by the prototypical connector se, which is capable of introducing a more basic conditionality. The theoretical basis of this research is mainly composed of theorists who interpret linguistic units in terms of pairings of forms and meanings, constructions, such as Traugott and Trousdale (2021) together with studies by Bybee (2016), which enable the interpretation of the conditional meaning through the correlation of formal and semanticpragmatic aspects, which were essential to prove that the hypothesis that the complex connectors instantiated by the [ADV de exclusão + se] subscheme are different from the cases in which there is only the presence of se, also proving that there are differences between the connectors instantiated by the subschema of this research. For the interpretation of the conditionality in the collected occurrences, the book of Dancygier (1998) was used, which gathers some parameters that characterize the conditional category, namely: non-assertiveness, prediction, mental spaces, causality and epistemic posture. In addition to Dancygier's (1998) parameters, other relevant parameters for the interpretation of occurrences, such as: function of adverbs and connectors, temporalmode correlation, position of conditional clause, constructional hierarchy of [ADV de exclusão + se] in the network of the conditional connectors, the subscheme slots [ADV de exclusão + se]. For this synchronic study, 600 occurrences of the current century were considered, collected in the Corpus do Português (available at: www.corpusdoportugues.org) in the Web/Dialects modality and after the analyzes it was found that the restrictive meaning of the adverbs was essential so that the restrictive sense was maintained when forming a complex conditional connector, as well as it was possible to notice that the connectors have differences in some conditionality parameters results.